The effects of mentoring to reduce stress in a state IT department during times of transformational change. (4th June 2007) - Riemenschneider, Cynthia; Allen, Myria; Reid, Margaret; Armstrong, Deborah
Over the last two decades, public sector organisations have responded to increasing demands for reforms and downsizing with accelerating cycles of organisational change. Researchers have suggested that public sector managers need to do more in assisting employees to cope with the change-induced stress. This study examined whether mentoring moderated the relationship between increased workloads associated with rapid organisational change and the subjective stress experienced by the employees. The study was conducted among public sector Information Technology employees of a south-central state in the United States and found positive relationships between career mentoring and subjective stress and between perceived workload and subjective stress. The relationship between perceived workload and subjective stress was moderated by psychosocial mentoring but not by career mentoring. Contrary to expectations, those who received more psychosocial mentoring reported experiencing more subjective stress during conditions of high perceived workload than did those who received less psychosocial mentoring.